Evaluation of yield decrease in common beans due to anthracnose (Colletotrichum lindemuthianum) below sub-temperate environment of Northwestern of Rwanda - Erastus Dushimeyesu; Sylvestre Habimana; Fabrice Musana Rwalinda; Mushayija James (Turkish Journal of Agriculture: Food Science and Technology)
The research was conducted in the year of 2021-2022 in Burera and Musanze District in Northern province as well as Rubavu District in Western Province with the aim of assessing the yield loss in common beans due to anthracnose by using four cultivars with various levels of resistance in field conditions in environment of Northwestern of Rwanda. Randomized complete block design as experiment design was used in this study where each selected cultivar was grown and the yield loss caused by anthracnose was assessed. A level of significance of P<0.05 . In field trials, on the particularly susceptible cultivar Gikundiro 2 particulary showed the maximum harm in terms of incidence and severity in both infection circumstances. The severity of pod infection ranging from 3-9 (0-) resulted in reduction in quantity of seeds which contain a pod ranging from 10.52 % -57.76 % and the loss in weight of seeds per pods ranging from 21.93 % - 68.77 %, both demonstrated a direct impact on seed yield. However, determinate cultivars showed a greater drop in yield (58.5%) than indeterminate cultivars (10.52%) although both were sensitive, based on this research, anthracnose causes economic yield loss on variety Gikundiro 2 and Vuzimpundu.